Ten-Year Uganda National Bamboo Strategy and Action Plan enabled by Research from FTA - CGIAR Research Program on Forests, Trees and Agroforestry (2019)
Scientific evidence generated and demonstration model developed by the International Bamboo and Rattan Organisation’s (INBAR) Dutch-Sino East Africa Bamboo Development Programme and joint INBAR/FTA research informed Uganda authorities of the significance and contribution of bamboo to sustainable development. Through using this research, and with technical and financial support from INBAR, the Ten-Year National Bamboo Strategy and Action Plan was commissioned, developed and written by the Ministry of Water and Environment of Uganda. This Action Plan is an important step to boosting the development of a viable and sustainable bamboo industry in the country.